Patterns of symptom deterioration can support multimorbidity management in COPD: Perspectives of patients and healthcare professionals - Sanne H. B. van Dijk; Marjolein G. J. Brusse-Keizer; Bente Rodenburg; Anke Lenferink (PLoS ONE, 2025)
Introduction Comorbidities significantly complicate COPD management. Remote monitoring could aid real-time disease and symptom management, assisting both patients with multimorbidity and healthcare professionals (HCPs). This study aimed to explore how insight in patterns of symptom deterioration, derived from remote monitoring, could enhance multimorbid COPD management as perceived by patients and HCPs. Methods Using daily symptom data collected via a mobile diary in the prospective RE-SAMPLE cohort study, patterns of symptom deterioration of COPD, chronic heart failure, anxiety, and depression were visualized per patient (follow-up duration of ≥4 months). Semi-structured individual interviews were conducted with Dutch patients with COPD and ≥1 comorbidity, and with HCPs from pulmonology, cardiology, and medical psychology who were involved in care for patients with multimorbidity. Interviews addressed current multimorbid COPD management, its challenges, and the way pattern visualizations of symptoms deterioration could support disease management. Transcripts were thematically analyzed using an inductive approach. Results 7 patients (69–80 years, 4 men) and 7 HCPs were interviewed in the hospital (patients and HCPs), at home (patients) or online (HCPs). Three overarching themes were identified, representing the elements of multimorbid COPD management that could be supported by the pattern visualizations: 1) relationship between diseases, 2) decision-making, and 3) self-management. According to patients and HCPs, pattern visualizations can be an informative source to explain the relation between COPD and comorbidities, function as a conversation starter facilitating communication between patients and HCPs as well as between medical disciplines, and educate patients in adequately recognizing their care needs. Conclusion Three elements of personalized multimorbid COPD management were identified through qualitative analysis, which can all be supported by visualizing patterns of symptom deterioration via remote monitoring. The visualizations could enhance patients’ understanding of their diseases, improve shared decision-making, improve in-hospital multidisciplinary collaboration, and support multimorbid COPD (self-)management.